Improving Numeracy and Metacognitive Skills of Grade V Students Through Balinese Ethnomathematics-Based Mobile Learning - Ni Nengah Diah Elsa Apricillia; I Made Suarjana; I Nyoman Laba Jayanta (Universitas Pendidikan Ganesha, 2024)
Students' low numeracy and metacognitive skills are one of the challenges in learning mathematics. In addition, the lack of contextual and relevant learning media to local culture also worsens the quality of learning. This study aims to analyze, develop, and evaluate the effectiveness of ethnomathematics-based mobile learning to improve students' numeracy and metacognitive skills. This is development research with ADDIE (Analyze, Design, Develop, Implement, Evaluate) design. The research subjects consisted of 12 fifth-grade students as field trial subjects. Data collection methods used questionnaires, tests, and documentation with instruments in the form of product validity and practicality questionnaires, as well as pre-test and post-test questions to measure students' numeracy and metacognitive skills. The data were analyzed using quantitative descriptive analysis for media validity and practicality and effectiveness tests, as well as a t-test to determine the difference in pre-test and post-test results. The results showed that ethnomathematics-based mobile learning is valid based on expert assessment, practical according to student and teacher responses, and effective in improving students' numeracy and metacognitive skills. This study concludes that mobile learning based on ethnomathematics can be an innovative and relevant learning medium to overcome mathematics learning problems. This research implies the need to integrate local culture in the development of learning media to create a more meaningful and contextualized learning experience.